P-529 Epigenetic clock and endometriosis: a new rhythm for reproductive timeline?. (30th June 2022) - Li Piani, L; Reschini, M; Busnelli, A; Fornelli, G; Viganò, P; Somigliana, E
Abstract: Study question: We aimed to verify whether endometriosis patients who succeeded in achieving a live birth through IVF were epigenetically younger than those who did not. Summary answer: Applying peripheral blood epigenetic clock, endometriosis women who delivered a baby after assisted reproductive technology (ART) procedures were epigenetically younger than those who did not. What is known already: The revolution of "epigenetic clocks", based on DNA methylation, has ushered in a new era. Epigenetic clocks reflect the possible gap between chronological and biological age. They have recently gained attention also in the reproductive field, since epigenetic mechanisms have been suggested to influence fertility. Moreover, endometriosis progression has been linked to epigenetic factors and the genetic/epigenetic theory has been suggested as a unification theory for its pathogenesis. Study design, size, duration: This is a secondary analysis of an observational cohort study, set at the Infertility Unit where we work. In the original study, we prospectively recruited women aged 37-39 years scheduled for an ART procedure between January 2017 and December 2018. For the present study, we considered only women with endometriosis and divided them into two groups: those who delivered and those who did not. Participants/materials, setting, methods: Recruited patients did not suffer of relevant systemic diseases, had normal weight and serum FSH levels, and their male partners were not severely infertile. Before the beginning of the IVF cycle, blood samples were collected in EDTA-containing tubes and stored. After DNA extraction, epigenetic age was calculated considering the methylation pattern of 5 CpG sites as reported by Zbieć-Piekarska in 2018. The methylation pattern at these sites were compared between the two groups. Main results and the role of chance: Thirty-eight women were enrolled. The cause of infertility was only endometriosis in 33 women or mixed with a concomitant mild male factor in 5 couples. Overall, 12 women (32% of our cohort) obtained a live birth. Women who had a live birth were characterized by higher antral follicular count compared to those who did not with a median value of 10 [6 – 14] and 13 [8-20] respectively (p < 0.02) and lower FSH (6.2 UI/L [5.8-7.5] and 8.3 [6.9-9.6], p 0.01 respectively). After ART, they obtained a higher number of suitable oocytes and cleavage stage embryos. Statistically significant difference emerged for epigenetic age (p < 0.05). Specifically, the median value and interquartile range was 34.5 [32.3 – 37.5] and 36.0 [35.0 – 38.3] for endometriosis women who did and did not have a live birth. The statistically significant epigenetic gap persisted even after adjusting for serum anti-mullerian hormone (AMH). Limitations, reasons for caution: This is a secondary analysis of a cohort study designed for infertility in general, the sample size was limited, and we included only women aged 37-39 years: confirmation in larger studies with broader selection criteria and specifically designed for endometriosis is warranted. Moreover, other epigenetic clocks could have been considered. Wider implications of the findings: Our study highlighted the relevance of epigenetics in endometriosis-related infertility. Epigenetic clocks could predict IVF success in affected women. Moreover, a deeper comprehension of these epigenetic mechanisms could lead to interventions aimed at reversing their effects, including modification of such lifestyle factors or hormonal medical treatments. Trial registration number: not applicable